Diseño de una mandrinadora portátil para la reparación de maquinaria pesada. - Aguinsaca Guachanama, José Manuel (2023)
The present project details the design of a machine tool for the repair of heavy machinery, mainly for lodgings or joints; this machine counts with a boring range between 60 mm and 120 mm, whose value is determined according to the requirements of the locality, in the design phase it is essential to establish the necessary parameters of the boring machine through literature review and observation of existing equipment. The definition of operating parameters was the starting point for the design, once the parameters were determined, a mathematical and physical analysis was carried out that served to determine the variables that would govern the design, this was done through software such as AutoCAD, SolidWorks, and Matcad, tools that facilitate modelling and data processing. Completed the systematic process, it was achieved the design of a machine tool adapted to the requirements initially raised, with the following working parameters: boring diameter of 60-120 mm, boring depth of 1.5 mm per pass and power of 750 W. Having the systems controlled is part of the design, this can be done by means of a frequency variator that will have the function of controlling the cutting speed between 120-250 rpm, likewise, the system in charge of the feed movement rotates at a rate of 0.063 mm/rev, this was achieved thanks to the inclusion of a servomotor, which is equipped with a built-in control unit that allows having absolute management of the feed speed. The design can be implemented thanks to the technology available in the locality and the necessary elements for its execution can be acquired within the national market. Additionally, detailed drawings of the machine tool were created where all the elements that compose the portable boring machine are described. Keywords: design, machine tool, boring machine, boring machine, housing, repair.